2021
DOI: 10.3389/fgene.2021.756685
|View full text |Cite
|
Sign up to set email alerts
|

A Haptoglobin Exon Copy Number Variant Associates With HIV-Associated Neurocognitive Impairment in European and African-Descent Populations

Abstract: A common two-exon deletion distinguishes the gene encoding the free hemoglobin capturing protein—haptoglobin (HP)–into two alleles: HP1 and HP2. To evaluate the impact of this copy number variant (CNV) on neurocognitive impairment (NCI) in people living with HIV, we imputed this variant in 432 European-descent (EUR) and 491 African-descent (AFR) participants from the CNS HIV Antiretroviral Therapy Effects Research Study using an optimized imputation pipeline and evaluated its associations with NCI. At baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 55 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…Though the hemoglobin binding affinity of the HP protein complex is not strongly influenced, due to their larger sizes, multimers demonstrate reduced binding capability, thereby leading to lower functional activity compared to dimers 22 . This SV has been previously associated with plasma lipid levels, and (in our prior work) with neurocognitive deficits in people living with human immunodeficiency virus (HIV) 20,24,25 . A small study also reported that the interaction of APOE ε4 and HP genotypes associated with longevity in a population in central Italy 26 …”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Though the hemoglobin binding affinity of the HP protein complex is not strongly influenced, due to their larger sizes, multimers demonstrate reduced binding capability, thereby leading to lower functional activity compared to dimers 22 . This SV has been previously associated with plasma lipid levels, and (in our prior work) with neurocognitive deficits in people living with human immunodeficiency virus (HIV) 20,24,25 . A small study also reported that the interaction of APOE ε4 and HP genotypes associated with longevity in a population in central Italy 26 …”
Section: Introductionmentioning
confidence: 72%
“…Only imputation dosages ≥0.9 were kept for further analyses and dosages < 0.9 were removed. This approach has been previously validated 25 …”
Section: Methodsmentioning
confidence: 99%
“…This approach was validated using gene-tissue expression (GTEx) RNA expression data (Supplemental Text 2, Table S1, S2, Figure S1). To impute the HP SV, we used a customized version of a published imputation reference that was developed using droplet PCR and validated using RNA-sequencing [20], [25], [Supplement File --Imputation Reference]. After TOPMed imputation, we first extracted SNPs that are included in the HP imputation reference.…”
Section: Imputationmentioning
confidence: 99%
“…Only imputation dosages ≥0.9 were kept for further analyses and dosages <0.9 were removed. This approach has been previously validated [25]. The "N"s are the number of individuals that are included in the analyses after omitting for missing in AD status.…”
Section: Imputationmentioning
confidence: 99%
See 1 more Smart Citation